Prognostic Value of the Progesterone Receptor by Subtype in Patients with Estrogen Receptor‐Positive, HER‐2 Negative Breast Cancer. (31st August 2018) - Van Asten, Kathleen; Slembrouck, Laurence; Olbrecht, Siel; Jongen, Lynn; Brouckaert, Olivier; Wildiers, Hans; Floris, Giuseppe; Van Limbergen, Erik; Weltens, Caroline; Smeets, Ann; Paridaens, Robert; Giobbie‐Hurder, Anita; et al.
Abstract: Background: In estrogen receptor‐positive (ER+), human epidermal growth factor receptor 2 (HER‐2) negative breast cancers, the progesterone receptor (PR) is an independent prognostic marker. Little is known about the prognostic value of PR by tumor grade. We assessed this in two independent datasets. Patients and Methods: Women with primary operable, invasive ER+ HER‐2 negative breast cancer diagnosed between 2000 and 2012, treated at University Hospitals Leuven, were included. We assessed the association of PR status and subtype (grade 1–2 vs. grade 3) with distant recurrence‐free interval (DRFI) and breast cancer‐specific survival. The interaction between PR status and subtype was investigated, and associations of PR status by subtype were calculated. The BIG 1‐98 data set was used for validation. Results: In total, 4, 228 patients from Leuven and 5, 419 from BIG 1‐98 were analyzed. In the Leuven cohort, the adjusted hazard ratio (HR) of PR‐positive versus PR‐negative tumors for DRFI was 0.66 (95% confidence interval [CI], 0.50–0.89). For the interaction with subtype ( p = .34), the HR of PR status was 0.79 (95% CI, 0.61–1.01) in luminal A‐like and 0.59 (95% CI, 0.46–0.76) in luminal B‐like tumors. In luminal A‐like tumors, observed 5‐year cumulative incidences of distant recurrence were 4.1% for PR‐negative and 2.8% for PR‐positive tumors, and in luminal B‐like 18.7% and 9.2%, respectively. In the BIG 1‐98 cohort, similar results were observed; for the interaction with subtype ( p = .12), the adjusted HR of PR status for DRFI was 0.88 (95% CI, 0.57–1.35) in luminal A‐like and 0.58 (95% CI, 0.43–0.77) in luminal B‐like tumors. Observed 5‐year cumulative incidences were similar. Conclusion: PR positivity may be more protective against metastatic relapse in luminal B‐like versus luminal A‐like breast cancer, but no strong conclusions can be made. In absolute risk, results suggest an absent PR is clinically more important in high compared with low proliferative ER+ HER‐2 negative tumors. Implications for Practice: An absent progesterone receptor (PR) predicts a worse outcome in women treated for an estrogen receptor‐positive, human epidermal growth factor receptor 2 negative breast cancer. As low proliferative tumors lacking PR are now also classified high risk, the prognostic value of PR across risk groups was studied. Despite a negative test for interaction of the prognostic value of PR by tumor grade, the magnitude of an absent PR on breast cancer relapse is much larger in high than in low proliferative breast cancers. Abstract : This article reports on the prognostic value of the progesterone receptor by tumor proliferation using tumor grade as a surrogate for the proliferative activity of estrogen receptor‐positive HER2‐negative breast cancer.